Investigation And Testing Rabies Virologically In Bali, Nusa Tenggara Barat (NTB) and Nusa Tenggara Timur (NTT) Province, Indonesia - Hamong Suharsono (Journal of Global Pharma Technology, 2019)
Background: Rabies is still endemic in the working area of the Denpasar Veterinary Center. For this reason, it is still necessary to conduct ongoing rabies surveillance activities aimed at: detecting the presence of rabies virus in dogs at risk of contracting rabies which related to efforts of liberation rabies in Bali Province, detecting the possibility of rabies virus presence in dogs in NTB Province so that this area remains rabies-free, detected rabies virus in dogs in the Flores Island and surrounding areas related to rabies control activities in NTT Province. Method: Rabies surveillance in dogs is mainly carried out by taking samples of dog brains that are at risk of transmitting rabies. The sample examined by the Fluorescent Antibody Test (FAT) method. Results: In 2016, the number of animal brain samples examined by the Denpasar Veterinary Center was 2,066. In Bali Province, the number of animal brain samples examined was 1,480 samples, 206 / 1,480 (13.92%) samples were positive for rabies. Positive cases of rabies came from dogs 205/206 (99.51%) samples and cats 1/206 (0.49%) samples. The average number of rabies positive cases per month is 17 cases. This number decreased sharply compared to 2015 there were 44 cases, per month. The most common rabies cases were found in Buleleng Regency as many as 41 cases, caused by dogs that have not vaccinated. The number of dog brain samples from districts/cities in NTB Province was 417 samples; there was no rabies positive. While animal brain samples from districts/cities on Flores Island and Lembata, NTT Province were examined as many as 169 samples, 45/169 (26.63%) samples were positive for rabies. Positive cases of rabies came from 44/45 dogs (97.78%) samples and 1/45 goats (2.22%) samples. Conclusion: The results of this surveillance show that rabies is still endemic in the Province of Bali and islands around the island of Flores, NTT. Mass vaccination programs, a collaboration between government agencies, communication, information and education about rabies to the community still need to be improved. Until now the NTB Province is still free of rabies. Control of rabies infectious animal traffic to the NTB Province and rabies-free areas in NTT is still needed.Keywords: Brucellosis, BPT, CFT, Bali, NTB. NTT.